Fenomena Pergaulan Bebas di Kalangan Remaja - Salsabila Awaliah; Nimas Dahlia Putri; Rima Ayu Lestari; Puspa Sari; Risma Anita Puriani; Rizki Novirson (Lembaga Pengembangan Kinerja Dosen, 2025)
Free association is one of the major challenges faced by teenagers today. Changes in the era and technological advances have made the boundaries of social norms increasingly blurred. Many teenagers are trapped in a free lifestyle due to lack of supervision from parents, peer influence, and uncontrolled use of social media. This has an impact on declining academic achievement, even causing them to drop out of school. In conditions like this, the role of Guidance and Counseling (BK) teachers is greatly needed. BK teachers are expected to be able to provide individual and group counseling services, deliver material on moral and ethical values, and work together with parents in guiding students. With the right approach from various parties, teenagers are expected to be able to protect themselves from the bad influence of association and grow into responsible and characterful individuals.